DESAIN NODE SENSOR UNTUK MONITORING LAHAN PERSAWAHAN BERBASIS MIKROKONTROLLER ATMEGA328P - Farid Wikarsa; Mohammad Fajar; Syaiful Rahman (KHARISMA Tech, 2019)
The purpose of this research is to design a low cost sensor node using ATmega328p microcontroller for monitoring a paddy field condition. Data collection techniques are done by literature study and sensor node prototype evaluation. The designed sensor node in this research consist of ATmega328P as an electronic circuit controller, DHT11 sensor to sense temperature and humidity, soil moisture sensor to read soil moisture parameter, 9V battery as power source of the node, 16MHz clock crystal to increase the microcontroller accuracy, voltage regulator to maintain a constant voltage level, and capacitor for the timer of the circuit. We use the C/C++ Arduino programming language to develop the software side of the node. The evaluation results show that the proposed sensor node is capable of sensing air temperature and humidity, soil moisture as well as send and receive the sensing data to/from the gateway node. The communication distance of the nRF24L01 module that we use for the node without an external antenna is up to 20.65 meters with an average packet loss of 20%.